A Comparison of the Effects of Supervised versus Home Schroth Exercise Programs with Adolescent Idiopathic Scoliosis - Kadriye Tombak; İnci Yüksel; Umut Ozsoy; Yılmaz Yıldırım; Sezen Karaşin (Children, 2024)
(1) Background: Schroth exercise can reduce the deformity of the spine and improve the life quality and the body image of patients with adolescent idiopathic scoliosis (AIS). (2) Methods: The study began with 49 participants, aged 10–16 years old, who were diagnosed with AIS. At the end of the study, 37 patients were randomly assigned to either the Supervised (n = 19) or Home-Based Schroth Exercise Group (n = 18) and completed the study. Both groups were treated for seven days a week over twelve weeks. For all patients, body rotation measurements were performed with a scoliometer, surface asymmetry analysis was carried out using an Artec Eva 3D scanner, health-related quality of life was evaluated by the Scoliosis Research Society-22 (SRS-22) questionnaire, and the perception of the cosmetic deformity was assessed by the Walter Reed Visual Assessment Scale (WRVAS). All the measurements were repeated before and after the 12-week treatment. (3) Results: Post-treatment scoliometric measurements showed a significant decrease in body rotation in both groups (p < 0.05). Similarly, both groups observed significant positive changes in SRS-22 and WRVAS scores (p < 005). RMS values were statistically significant in both groups; the difference was only statistically significant in the thoracic anterior arm subparameter (p < 0.05). (4) Conclusion: The Schroth exercise for both groups with AIS improved body symmetry, quality of life, and body image.